Determination of antimalarial drugs in pharmaceutical formulations and human blood by liquid chromatography: a review. Issue 39 (6th October 2021) - Penna, Eduarda Alves; de Souza, Jéssica Cordeiro Queiroz; de Oliveira, Marcone Augusto Leal; Chellini, Paula Rocha
Abstract : The evolution of different analytical methods that have been applied to the determination of antimalarial drugs in pharmaceutical formulations and human blood by liquid chromatography. Abstract : Malaria is a life-threatening disease being treated by oral medication. This is the best treatment to reduce morbidity and mortality, prevent disease progression to the most severe form, lower the transmission of the disease and hinder the appearance of strains resistant to antimalarials. According to the World Health Organization, the most common antimalarial drugs are chloroquine, primaquine, mefloquine, lumefantrine, artemether, and artesunate in single dosage forms or fixed-dose combination. Within this context, the present review aims to show the evolution of different analytical methods that have been applied to the determination of these antimalarial drugs in pharmaceutical formulations and human blood by liquid chromatography in the last 10 years, along with statistical analyses of the methods.